Antitrypanosomal and Anthelminthic Properties of Ethanol Extracts of Carica papaya Linn. and Ceiba pentandra (L) Gaertn. - Ahmed Wahab Obeng; Yaw Duah Boakye; Theresa Appiah Agana; Vivian Etsiapa Boamah; James Oppong-Kyekyeku; Abena Amponsaa Brobbey; Francis Adu; Stephen Yao Gbedema; Christian Agyare (Journal of Chemistry)
The most common diseases that affect low-income countries are helminthosis and trypanosomosis. In Ghana, and in many other African countries, herbal treatment of various diseases is still common. In the present study, we sought to determine the antitrypanosomal and anthelminthic activities of Carica papaya and Ceiba pentandra. The ethanol extracts of Carica papaya stem bark (PPSe) and leaves (PPLe) and ethanol extracts of Ceiba pentandra stem bark (CPSe) and leaves (CPLe) were screened against Trypanosoma brucei brucei and Pheretima posthuma worms in vitro. CPSe exhibited strong antitrypanosomal activity, while the other extracts exhibited moderate activity against T. b. brucei. All the extracts showed weak selective indices (SI) when tested on Jurkat cell lines, which is indicative of a potential toxic effect. When the extracts were screened against P. posthuma worms, only PPSe and CPSe were able to kill the worms after the exposure time at concentrations of 2.5, 5, and 10 mg/mL. PPSe was again the only extract that potentiated the anthelminthic activity of albendazole against P. posthuma worms. Preliminary phytochemical screening and GC-MS analysis revealed the presence of compounds with antitrypanosomal and anthelminthic properties. The results confirmed the potential of C. papaya and C. pentandra as remedies for trypanosomosis and helminthosis and also gives credence to their folkloric use.